EXPLORING TEACHERS' PRACTICAL DECISION MAKING IN TERMS OF TEACHING PROCEDURES - Wulan Samsuri; Sumarta Sumarta; Acep Bahrum (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The role of teaching English in senior secondary schools as a component of Indonesian education policy has increased. The curriculum states that the main objectives of English language education are to improve students' basic communication skills, to develop English language, or learning, interests and habits, and to introduce global culture to society. Since language education is based on interpersonal relationships and communication with others, which stem from self-knowledge and understanding, exploring oneself together with oneself can be an important professional in the field. Borg (2003) states that there are several problems related to language education that have not been studied in contact with teacher cognition. This study is about the teacher's consideration in making decisions about teaching procedures. This study uses a qualitative research design to collect data using interviews and observations. Keyword: Decision making, Teachers, Teaching procedures.